Clinical Characteristics for Differentiating Febrile Children With Suspected Kawasaki Disease Diagnosis - Yan, Jia-Huei; Chang, Ling-Sai; Lin, Yi-Ju; Guo, Mindy Ming-Huey; Huang, Ying-Hsien; Kuo, Ho-Chang (Frontiers in Pediatrics, 2020)
Background Kawasaki disease (KD) is a form of vasculitis that primarily affects children under the age of 5 years old. Patients may be missed or diagnosis delayed when initial clinical symptoms do not fulfill the traditional criteria or a normal echocardiography was found. In this study, we aimed to analyze factors that clinicians could use to differentiate febrile children suspected of KD. Method We retrospectively enrolled in this study a total of 50 febrile children who were initially suspected of KD, but they did not meet the American Heart Association (AHA) criteria for a diagnosis. However, some of these patients were diagnosed with KD during their second visit. We analyzed patients' characteristics, clinical symptoms, and laboratory data (initial data in the first visit). Results In total, 50 patients were enrolled in the study. Of those, ten patients were diagnosed with KD on their second visit (group 1), while the other 40 patients still did not fit a KD diagnosis (group 2). A higher neutrophil-to-lymphocyte ratio (NLR, p=0.037) and higher C-reactive protein levels (CRP, p=0.02) were found in group 1 when compared to group 2. A patient with a NLR greater than 1.33 combined with a CRP more than 33 mg/L was more likely to have KD (Sensitivity 90%, specificity 69.2%, p=0.001; Odds ratio 20.25, 95% confident interval 2.3-178.25). Conclusion Among patients suspected of KD that did not initially meet the criteria, clinicians should pay special attention to elevated neutrophil-to-lymphocyte ratios and CRP levels and closely follow up such patients.